LESSON LEARNED FOR ASEAN FROM THE INTEGRATION OF HUMAN RIGHTS IN THE EUROPEAN UNION (THE EU) - Rachminawati, Rachminawati (UI Scholars Hub, 2021)
Human rights are one of the EU’s tools to integrate its member states as well as its citizens. The integration of human rights into EU law and policy build the concept of “the new EU” which is to establish “economic space” together with the space of liberty, justice and security which is implemented in the third pillar of the Maastricht Treaty .EU experience shows that the integration of human rights into their law and policy not only enhance the protection of human rights and democratic legitimacy but also economic, social welfare and peaceful life. Integration of human rights demonstrates the possibility of a plural nation which have a background of century-old conflicts to become one strong institution. The EU and ASEAN follow a similar path of regional integration. The success of the EU integration includes human rights integration and has made the EU a model for ASEAN integration. Despite, their differences, the ASEAN can learn the positive contribution of integrating human rights in the EU as the ASEAN is moving from economic cooperation to other related areas including human rights through ASEAN Community in 2015.